Spatial-temporal characteristics and prediction of ischemic heart disease burden in the working population aged 15 to 59 years in China - Zhang, Yuanhang; Du, Ruyi; Zhang, Xiaoshuai; Li, Tiankai; Gao, Lei (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveBased on GBD 2021 data, to analyze the disease burden of ischemic heart disease (IHD) in the Chinese population.MethodsThe mortality rate, incidence rate, prevalence rate and Disability-Adjusted Life Years (DALYs) data of IHD in the Chinese population aged 15–59 from 1990–2021 were extracted and age-standardized. Joinpoint regression was used to analyze the trend. The Age-Period-Cohort model (APC) decomposed age, period and cohort effects, and the Arima model predicted the disease burden.ResultsFrom 1990–2021, the age-standardized mortality rate (ASMR) and the DALYs rate (ASDR) decreased by an average annual percentage change (AAPC) of −0.76 (95% CI: −0.94 to −0.57) and −0.71 (95% CI: −0.87 to −0.55), respectively. The age-standardized prevalence (ASPR) and incidence (ASIR) increased by 0.53 (95% CI: 0.49–0.57) and 0.78 (95% CI: 0.64–0.91), respectively. The decline in ASMR and ASDR in women was greater than that in men, while the increase in ASPR and ASIR was more significant. The risks of death, DALYs and disease onset increase with age. The risk of onset first increased and then decreased. The risks of death and DALYs fluctuated and decreased over time. The risks of death and DALYs peaked from 2002–2006, and incidence risk peaked from 2007–2011. The risk of disease onset increased with the progress of the birth cohort, while the risks of death and DALYs decreased. In the next 15 years, ASIR, ASMR and ASDR of IHD in China will generally show a downward trend. The decline in ASMR and ASDR in women will be greater than that in men, but ASIR in women will increase and ASIR in men will decrease.ConclusionThere are gender differences in the IHD burden among the working population in China. Health education and early screening for middle-aged and elderly men should be strengthened, and lifestyle intervention should be carried out for middle-aged and young women.